KLASIFIKASI ILMU PENGETAHUAN DALAM ISLAM: ISLAM DAN SAINS - Muhammad Akmal Fachrezy; Putri Zahrotun Naqiah (PT. Hasba Edukasi Mandiri, 2026)
This research discusses the classification of knowledge in the perspective of Al-Farabi and Al-Ghazali and examines its relevance to the problem of dichotomy of knowledge in general education in Indonesia. The method used in this research is a qualitative approach based on library research with comparative-philosophical analysis. The results of this research show that Al-Farabi classified knowledge rationally and hierarchically by emphasizing the structure and logical relationships between fields of knowledge, while Al-Ghazali classified knowledge based on moral dimensions and ethical responsibility through the division of fardhu 'ain and fardhu kifayah. Despite their different approaches, both reject the separation between rational aspects and moral values in knowledge. The conclusion of this research is that in the context of Indonesian education, the thoughts of these two figures are relevant to overcome the fragmentation of knowledge and pragmatic orientation of modern education. The integration between Al-Farabi's rational structure and Al-Ghazali's ethical foundation can serve as a conceptual basis for developing a more holistic education oriented towards character formation.